Drosophila melanogaster H1 histone is phosphorylated stably. - Talmage, D A (1987)
Phosphorylation of histone H1 is developmentally regulated in Drosophila spp. It cannot be detected in preblastoderm embryos or polytene salivary gland cells, but in cellular blastoderm, postblastoderm embryo, and amitotic adult head nuclei, it occurs with a frequency of roughly 4 x 10(5) molecules per nucleus. We used pulse-labeling to study the relationship between H1 synthesis and modification in cultured cells. These results reveal that the H1-associated phosphate is stable and suggest that Drosophila H1 is synthesized, translocated to the nucleus, associated with chromatin, and then phosphorylated. Partial tryptic digestion of Drosophila H1 revealed that the phosphorylation site is located within the globular, central domain of the protein. Thus, the developmentally regulated phosphorylation of Drosophila H1 presents two contrasts with previously studied H1 phosphorylation. It is not correlated with DNA replication, and it is located in the central domain of the protein.